2002
DOI: 10.1046/j.0022-202x.2001.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

All-trans Retinoic Acid Induces Differentiation and Apoptosis of Murine Melanocyte Precursors with Induction of the Microphthalmia-Associated Transcription Factor

Abstract: The effects of all-trans retinoic acid on the differentiation and proliferation of immature melanocyte precursors were studied. NCC-melb4 cells are an immortal cloned cell line established from mouse neural crest cells using a single-cell cloning method. These cells were positive for tyrosinase-related protein 1, tyrosinase-related protein 2 and KIT, but were negative for tyrosinase and had no dihydroxyphenylalanine reaction. They contained only stage I melanosomes without any melanosomes in more advanced stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…In other studies on melanocyte differentiation, treatment with retinoic acid (Watabe et al, 2002), or seeding ES cells, melanocyte precursors or neural crest cells on a cell layer (Yamane et al, 1999) have been used as the inducing stimulus. These experiments led to melanocytes, but the mechanisms that triggered the differentiation process could not be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies on melanocyte differentiation, treatment with retinoic acid (Watabe et al, 2002), or seeding ES cells, melanocyte precursors or neural crest cells on a cell layer (Yamane et al, 1999) have been used as the inducing stimulus. These experiments led to melanocytes, but the mechanisms that triggered the differentiation process could not be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Some melanocytes were obtained after seeding undifferentiated ES cells on a bone marrow-derived stromal cell line and treating the cells with dexamethasone (Yamane et al, 1999). Mature melanocytes were obtained from a cell line of immature melanocytes treating the cells with retinoic acid (Watabe et al, 2002). An increase of expression of microphtalmia transcription factor (Mitf) was observed indicating an important role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, our observation is similar to that observed in the ligands of other nuclear hormone receptors including retinoic acid receptor in melanocytes. Retinoic acid has inhibitory effects on the growth of melanocytes, which was accompanied by the induction of apoptosis in melanocytes [21]. Watabe et al [21] suggested that mature differentiated melanocytes are removed through apoptosis, which may be clinically beneficial, as topical application of retinoic acid reportedly improved hyperpigmented skin lesions like melasma.…”
Section: Ciglitazone Induces Apoptosis In Human Melanocytesmentioning
confidence: 99%
“…Melanogenesis may be related to the apoptosis. 8,9 Expression of apoptosis regulatory molecules (ie, Bcl down-regulation and Bax up-regulation) are closely involved in melanogenesis. 8 In addition, it was reported that mature melanocytes may tend to undergo apoptosis after alltrans retinoic acid treatment.…”
mentioning
confidence: 99%
“…8 In addition, it was reported that mature melanocytes may tend to undergo apoptosis after alltrans retinoic acid treatment. 9 Further study is needed for more precise understanding of the ballooning changes in association with apoptotic activity.…”
mentioning
confidence: 99%